The effect of objectives of shariah on Islamic transactions = أثر المقاصد الشرعية في فقه المعاملات المالية - Alshibany, Abdulaziz Mohammed; Mat Jubri@Shamsuddin, Mustafa (2019)
The purpose of this research is to apply the science of Maqasid al-Shariah to the jurisprudence of financial transactions and what is emerging from them and the issues that have been occuring and new at all times and everywhere, and to clarify the relationship between the Maqasid al-Shariah and Islamic financial transactions.The researcher followed in his research the inductive method, by collecting the written efforts of the Maqasid al-Shariah in general and trying to focus on the jurisprudence of financial transactions in particular, and to clarify the impact of Maqasid al-Shariahin the issues of jurisprudence of financial transactions addressed by jurists in their writings. Among the most important findings of the research: that Islamic law has considered a number of general purposes in the legislation of financial transactions in particular, and the economic system in general. And that the purposes of legitimacy have a great impact in rationalizing and guiding the fatwa, especially in ruling on the developments of financial transactions. And also urged scholars and researchers to apply the Maqasid al-Shariah of Islamic financial transactions and developments.